MANAJEMEN PENGELOLAAN ZAKAT DALAM PENINGKATAN KESEJAHTERAAN MUSTAHIK PADA BADAN AMIL ZAKAT NASIONAL (BAZNAS) KABUPATEN PAMEKASAN - Ramadhoni, Ahmad Rizqi (IDEALITA: Jurnal Pendidikan dan Sosial Keagamaan, 2023)
The Pamekasan district national amil zakat agency (BAZNAS) is a formal legal institution with the main tasks and functions (TUPOKSI) of implementing zakat management in collection; distribution and utilization of zakat at the Regency/City level. The formulation of the problem in this study. First, how does the management influence the management of zakat which consists of planning (planning); organizing (organizing); directing (actuating) and controlling (simultaneously) in improving welfare at the national amil zakat agency (BAZNAS) Pamekasan district. Second, how is the dominant influence of the management of zakat management which consists of planning (planning); organizing (organizing); directing (actuating); and controlling (partially) in improving the welfare of mustahik based on Islamic law and positive law at the national amil zakat agency (BAZNAS) Pamekasan district. This research includes field research with a quantitative approach. The results of the statistical test analysis of the results of the study found that the coefficient of determination (R2) was 0.983 or 98.3%, while the rest were influenced by other variants not included in this study. This shows that the management of zakat management which consists of planning (planning); organizing (organizing); directing (actuating); and control (controlling) has a significant (significant) influence in improving the welfare of mustahik at the national amil zakat agency (BAZNAS) Pamekasan district. The results of the simultaneous hypothesis test show that fcount 550.850 > ftable which reads: management of zakat management has a significant influence on increasing the welfare of mustahik at the national zakat amil agency (BAZNAS) Pamekasan district. The results of the partial hypothesis test show that tcount 5.201 > ttable which reads: Controlling in the management of zakat management has the most dominant influence compared to planning; organizing (organizing); directing (actuating) in improving the welfare of mustahik at the national amil zakat agency (BAZNAS) Pamekasan district.